Leasing in Development : Lessons from Emerging Economies - Fletcher, Matthew; Freeman, Rachel; Sultanov, Murat; Umarov, Umedjan (International Finance Corporation, Washington, DC, 2012)
By studying the approach of IFC leasing technical assistance projects implemented to date, the authors hope to provide a useful reference. This manual highlights which elements to look for locally, why experiences may be different between countries, and what (based on our collective experience) may be appropriate courses of action. Examining the approach of current and past projects, this manual also aims to identify the key policy issues on leasing development. Within these policy issues, there will be certain standards that are non-negotiable-tenets that form the foundation of credibility, integrity, and success around the world. There will be other elements on these issues that are based on general principles that can be applied only in specific ways depending on local conditions. This manual should help leasing development practitioners identify key local characteristics, assess their potential impact, and, therefore, make the decisions required on which route to take.